2015
DOI: 10.1039/c4ta06893a
|View full text |Cite
|
Sign up to set email alerts
|

Binary PdM catalysts (M = Ru, Sn, or Ir) over a reduced graphene oxide support for electro-oxidation of primary alcohols (methanol, ethanol, 1-propanol) under alkaline conditions

Abstract: High metal loaded (60 wt%) binary PdM (M = Ru, Sn, Ir) catalysts were synthesized on reduced graphene oxide (RGO) for the electro-oxidation of simple alcohols, such as methanol, ethanol, and 1-propanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 47 publications
3
37
0
1
Order By: Relevance
“…This phenomenon was also observed for Pt-based [14,60], Pd-based [23], and Au-based [61] catalysts, which can be attributed to several possible reasons. First, particles smaller than 0.5 nm are hard to be recognized in TEM images but can be reflected by calculation based on XRD patterns.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…This phenomenon was also observed for Pt-based [14,60], Pd-based [23], and Au-based [61] catalysts, which can be attributed to several possible reasons. First, particles smaller than 0.5 nm are hard to be recognized in TEM images but can be reflected by calculation based on XRD patterns.…”
Section: Resultssupporting
confidence: 51%
“…One method of reducing the cost of catalyst layer is to lower down the loading of Pt, while another method is to replace Pt with more abundant and less expensive Pd. To prepare highly active Pd-based catalysts, a number of strategies have been investigated, including controlling the morphology of Pd [15][16][17][18][19], alloying other elements to prepare Pd-M catalyst [20][21][22][23][24][25], and improving the surface area of the catalyst support [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…[32] Such an alloy may reduce the Pd content and further enhance its catalytic activity.I na ddition, the Pd lattice becomes strainedw ith modulated electronic configuration, making more active sites to improve the Pdbased catalytic activity. [33] For instance, some bimetallic catalysts are such as Ru-Cu/biochar, [34] Pd-Ru/g-Al 2 O 3 , [35] RuPd@GO, [36] PdRu/RGO, [37] PdRu/C, [38,39] Ru@2Pd@Ru/C, [40] and Pd x Ru 1Àx /C, [41] which were adopted for both catalytic and electrocatalytic applications, showing as urprisingly superior activity,s tability with respectt ot heir single metal counterparts. It has been demonstrated that Pd catalysts show high catalytic activity for the reduction of Cr VI .R ui sp roved to greatlye nhance the catalytic properties of Pd through the bifunctional and electronic effect, in formica cid (HCOOH; FA)o xidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, electrode activity has recovery limitations. Despite this, several studies have reported that Pd-based electrodes exhibit high durability and superior electrical conductivity [26][27][28]. The advantage of four-component electrodes is that they involve a smaller amount of the precious metal Pd, which forms the binary system, and the other three components play a role in reducing the dispersion and stability of Pd.…”
Section: Introductionmentioning
confidence: 99%